Consensual Qualitative Research: A concise overview of the method and its potential use in the study of qualitative data drawn from pre-existing written texts - Δημητριάδου, Ελένη; Σταλίκας, Αναστάσιος; Οικονόμου, Μαρίνα (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The abstract is available in the PDF